ADSORPSI ION Pb(II) OLEH LEMPUNG COKELAT ASAL DESA OUW KECAMATAN SAPARUA - Sunarti Sunarti; Yeslia Utubira; C Tehupeiloy (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2011)
The adsorption capability of brown clay from Ouw village Saparua District has been researched. The adsorption was done by mixing clay into Pb solutions with pH variations are 3,4,5,6,7,8. The analysis result by using Atomic Absoption Spectrophotometer (AAS) showed the adsorption capability of brown clay with pH variations respectively 192; 301,5; 980; 884,5; and 582 ppm. The optimum condition of Pb(II) ion adsorption is reached on 5 of pH